2020
DOI: 10.1111/ajo.13199
|View full text |Cite
|
Sign up to set email alerts
|

Women’s epidural decision‐making in labour: A Townsville perspective

Abstract: Despite being an efficacious method of pain relief in labour, 1 regional analgesia is used in approximately a third of Australian labours (36%), 2 compared to Canada and the USA (approximately 60%) 3,4 and the UK (approximately 15%). 5 Australian data suggest that a pre-labour intention to use pharmacological options 6 and prior positive experience 7 were associated with an increased epidural preference. Data from outside of Australia suggest that perception of pain, 8,9 personal and peer experience 10,11 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…This could indicate that the population is becoming more educated toward EDA. A study in Townsville, Australia, showed that 44% of participants disagreed that they would never use EDA, while 56% were unsure about whether EDA helps with labor progression, and 63% agreed that they were worried about the possibility that it will affect their ability to walk and move around [8]. These results were similar to our study with a small difference in the percentages (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…This could indicate that the population is becoming more educated toward EDA. A study in Townsville, Australia, showed that 44% of participants disagreed that they would never use EDA, while 56% were unsure about whether EDA helps with labor progression, and 63% agreed that they were worried about the possibility that it will affect their ability to walk and move around [8]. These results were similar to our study with a small difference in the percentages (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…An augmented labor increases the desire for an epidural, as noted in other studies. 2,5,6,11 However, epidurals were used less by our study participants being induced than those having labors augmented, possibly because a labor induction does not necessarily correlate with a poorly progressing labor. There is no currently known way to ensure a spontaneous labor and birth for everyone, but more evidence-based research on how to encourage and facilitate a spontaneous labor is possible.…”
Section: Discussionmentioning
confidence: 89%
“…As in previous studies, spontaneous labor again emerged as a key determinant for the desired childbirth outcome of a healthy mother and baby with minimal intervention. 5,6,11 Regardless of the number of pain relief measures chosen, a large number of study participants indicated a desire for an unmedicated labor (n = 301; 58.8%), either listing an unmedicated labor alone or in conjunction with another choice. This illustrates the trend among a Overall rating attributed to the last method used, assuming it to be representative of all methods used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations